Circulating de novo Donor Specific Antibodies and Carotid Intima-media Thickness in Pediatric Kidney Transplant Recipients, A Pilot Study - Sgambat, Kristen; Clauss, Sarah; Moudgil, Asha (Frontiers in Pediatrics, 2020)
Background: The presence of circulating de novo donor specific anti-HLA antibodies (dnDSA) has been implicated in an immune-mediated form of accelerated systemic arteriosclerosis in adult heart and kidney transplant recipients, however this has not been previously investigated in pediatric kidney transplant recipients. Carotid intima-media thickness (CIMT) is a reliable method for detection of arteriosclerosis. We hypothesized that children who develop dnDSA after kidney transplant would have increased CIMT compared with those who remain dnDSA negative. Methods: A prospective, controlled pilot cohort study of 38 transplant patients and 20 healthy controls was conducted to investigate the association between CIMT and development of dnDSA after kidney transplant. CIMT, anthropometrics, blood pressure and lipid panel were measured at 1, 18, and 30 months post-transplant. DSA was checked at 6, 12, 18, 24 and 30 months post-transplant. CIMT of DSA positive transplant recipients was compared to DSA negative and controls. Results: Of the 38 transplant recipients, 7 patients developed dnDSA by 18-30 months post-transplant. Among 5 dnDSA positive patients who did not receive treatment for DSA prior to CIMT measurement (n=6 observations), the median CIMT was 0.505 mm (95% CI 0.454-0.560 mm) at 18-30 months post-transplant, compared to 0.455 mm (95% CI 0.440-0.470) in DSA negative transplant recipients (n=54 observations of 30 patients) and 0.450 mm (95% CI 0.436-0.460) in the healthy controls (20 observations of 20 patients). Presence of dnDSA was independently associated with a 7.8% increase in CIMT compared to those without dnDSA (p=0.006), after adjusting for race, hypertension, dyslipidemia, and abdominal obesity. Conclusions: Development of dnDSA was associated with increased CIMT, an indicator of arteriosclerosis, in a cohort of dnDSA positive pediatric kidney transplant recipients. The association between dnDSA and CIMT was independent of traditional CV risk factors, including hypertension, dyslipidemia, and abdominal obesity.